Incremental optimization of independent sets under the reconfiguration framework - Ito, Takehiro; Mizuta, Haruka; Nishimura, Naomi; Suzuki, Akira (Journal of combinatorial optimization, 2022)
Suppose that we are given an independent set I 0 of a graph G , and an integer l ≥ 0 . Then, we are asked to find an independent set of G having the maximum size among independent sets that are reachable from I 0 by either adding or removing a single vertex at a time such that all intermediate independent sets are of size at least l . We show that this problem is PSPACE-hard even for bounded-pathwidth graphs, and remains NP-hard for planar graphs. On the other hand, we give a linear-time algorithm to solve the problem for chordal graphs. We also study the parameterized complexity of the problem with respect to the following three parameters: the degeneracy d of an input graph, a lower bound l on the size of independent sets, and a lower bound s on the size of a solution reachable from I 0 . We show that the problem is fixed-parameter intractable when only one of d , l , or s is taken as a parameter. On the other hand, we give a fixed-parameter algorithm when parameterized by s + d ; this result implies that the problem parameterized only by s is fixed-parameter tractable for planar graphs, and for bounded-treewidth graphs.